ASSESSMENT OF MEDICAL CARE QUALITY IN CRANIOCEREBRAL TRAUMA ON THE BASE OF DATA ANALYSIS - O. V. Moguchaya; E. K. Gumanenko; I. A. Simonova; V. V. Shchedrenok; O. V. Romashova; T. A. Kaurova (Вестник хирургии имени И.И. Грекова, 2018)
An analysis of 658 medical records of inpatient treatment from 15 hospitals of St. Petersburg was made using a computer-aided technology of the assessment of medical care quality. It was revealed that a proper quality of medical care in craniocerebral trauma was only in 52,9% cases. Different defects of medical care were noted in the rest of observations. It influenced on the condition of the patients (1,0%), the delivery and assessment of health care (40% and 38%, respectively), health resources (18%), social resources (1,0%). Defects of medical records were indicated in 38% patients. It caused a reduction of medical care. Risks of occurrence of medical care defects are low in children hospitals in the case of combined craniocerebral trauma.